Experiences of Nurse Managers During the COVID-19 Pandemic in Turkey: A Qualitative Study - Yeliz Akatın; Nezaket Yıldırım (Association of Nurse Managers, 2022)
Aim: The purpose of this research is to identify the experiences of nurse managers during the COVID-19 pandemic in Turkey. Method: Qualitative descriptive study design. In the study, semi-structured interviews were conducted with 14 nurses using the purposive sampling method. The content analysis method was used in the analysis of the data. Results: In the study, the following four themes were determined: changes in workforce management, adverse effects of the pandemic, being a manager in the pandemic, and heroism. In addition, nine sub-themes were determined based on these themes. Conclusion: The COVID-19 pandemic is an important process for nurse managers as it provides opportunities for new roles, innovative approaches, different communication channels, and new learning experiences.